Evaluation of the efficacy of lipotransfer to manage radiation‐induced fibrosis and volume defects in head and neck oncology. Issue 10 (7th August 2019) - Griffin, Michelle F.; Drago, Jelovac; Almadori, Aurora; Kalavrezos, Nicholas; Butler, Peter E.
Abstract: Background: Multimodality treatment for head and neck cancer leads to substantial functional and esthetic impairment mainly manifested as radiation‐induced skin fibrosis (RIF) in combination with volumetric defects and reduction in neck mobility. This study assessed the impact of lipotransfer as part of secondary surgical procedure(s) in patients treated for head and neck malignancies. Methods: Retrospective analysis was performed between 2005 and 2016. All patients with a history of head and neck malignancy, multimodal treatment including at least surgery or radiotherapy, and at least 2‐year disease‐free survival were included. Thirty‐eight patients (22 men, 16 women) matched the inclusion criteria. Results: Thirty seven (97%) reported esthetic and functional improvements in their RIF and volumetric defect at follow‐up of 32 months. Major improvement in esthetic and functional outcome was reported by 24 (63%) patients and surgeons and minor by 13 patients and surgeons (34%) without causing any complications. Lipotransfer was also found to significantly improve patient's psychological health postoperatively as showed by significant improvements in Derriford Appearance Scale (DAS24), Short Form Health Survey (SF‐36), and University of Washington Quality of Life Questionnaire (UW‐QOL V4) scores ( P < .001). Conclusions: Lipotransfer is effective for volume restoration and treating scar and RIF from head and neck defects.